2020
DOI: 10.1101/2020.02.21.960377
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome wide association study reveals plant loci controlling heritability of the rhizosphere microbiome

Abstract: 45Host genetics has recently been shown to be a driver of plant microbiome composition. However, 46 identifying the underlying genetic loci controlling microbial selection remains challenging. 47 Genome wide association studies (GWAS) represent a potentially powerful, unbiased method to 48 identify microbes sensitive to host genotype, and to connect them with the genetic loci that 49 influence their colonization. Here, we conducted a population-level microbiome analysis of the 50 rhizospheres of 200 s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 69 publications
4
16
0
1
Order By: Relevance
“…This likely is attributable, in part, to varying diversity and rate of plant root exudation across different accessions, species, and growing conditions [ 3 , 69 ]. In addition, other studies provide additional evidence that rhizospheres—which host a more diverse and greater pool of microbes than the root itself to exert influence on—may be ideal for better understanding host contributions to microbiome assembly [ 70 ], including microbiome-based genome-wide association studies [ 71 ]. In order to better understand contributions of ploidy level to microbiome assembly, versus what may be attributable to other genotype dependent differences, we recommend that future work investigate how finer genetic differences across ploidy levels may relate to differences in microbiome composition and activity (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This likely is attributable, in part, to varying diversity and rate of plant root exudation across different accessions, species, and growing conditions [ 3 , 69 ]. In addition, other studies provide additional evidence that rhizospheres—which host a more diverse and greater pool of microbes than the root itself to exert influence on—may be ideal for better understanding host contributions to microbiome assembly [ 70 ], including microbiome-based genome-wide association studies [ 71 ]. In order to better understand contributions of ploidy level to microbiome assembly, versus what may be attributable to other genotype dependent differences, we recommend that future work investigate how finer genetic differences across ploidy levels may relate to differences in microbiome composition and activity (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Several genome‐wide association studies (GWAS) have identified candidate plant genes that influence the assembly of plant‐associated microbiota (Walters et al ., 2018; Beilsmith et al ., 2019; Roman‐Reyna et al ., 2019; Deng et al ., 2020). These genes are shared between different plant varieties and are correlated highly with the abundance of specific subsets of the rhizosphere microbiome (Walters et al ., 2018; Deng et al ., 2020). Manipulation of these candidate genes can provide a way forward to generate designer plants with defined microbiomes and their associated benefits (Box 3).…”
Section: Roadmap For Translationmentioning
confidence: 99%
“…Эти различия зарегистрированы при выращивании растений на контрольной незагрязненной почве и особенно выражены при культивировании подсолнечника на техногенно загрязненной почве КМЗ (рисунок, а -в). Обнаруженные различия могут быть обусловлены как свойствами почв и уровнем их загрязнения, так и различиями в составе корневых экссудатов растений двух мутантных культиваров, имеющих приоритетное значение для формирования специфического ризосферного микробиома того или иного растения (Schlemper et al, 2017Deng et al, 2020).…”
Section: результаты и их обсуждениеunclassified